Science Learning for Early Childhood Students with Science Games Play - Kasmiati (Postgraduate, University of Mataram, 2024)
From an early age children must be equipped with various sciences knowledge, including science. This research aims to review various sources about the science play as a form of learning method at the PAUD level as well as knowing the effectiveness of the science play method in learning science learning in early childhood. Science learning is a process that emphasizes skills of acquiring knowledge and developing scientific attitudes. Science learning is a process of understanding the nature of science itself, namely curiosity, process, product and application/attitude. The literature that was collected in the form of journals, articles and books relevant to the topic, then interpret and analyzed the sources, interpretation of the sources and compiled them in a systematically and structured. Early childhood is a period of child development that is interesting to observe. This is because it involves complex processes, both those that occur inside (physiological and psychological) and outside (environment). The science play method is effective in learning science in early childhood, including; it can improve science abilities and science learning outcomes, introduce and improve basic science process skills and improve children's science concepts.